Brazil : Stability for Growth and Poverty Reduction - World Bank (Washington, DC, 2013)
The importance of macroeconomic stability for growth, and poverty reduction is now accepted in Brazil. As of 1964, the country followed responsible macroeconomic policies, in the pursuit of stability, reconfirmed by the new Government in January 2003. The report focuses strictly on three key macroeconomic issues, critical to assure stability, avoid crises, and hence allow poverty reduction on a sustainable basis. Though much has been achieved, stability, and higher growth in Brazil now depend on reforms along three main axes: Structural fiscal reforms, to allow flexible public spending towards a higher primary surplus; moving towards a different public debt composition; and, ensuring an external adjustment, sustainable and in tandem with higher growth. The report argues for reducing volatility, and uncertainty to achieve sustainable growth, and poverty reduction, and, based on its analysis, it further argues for a debt management strategy that includes gradual lengthening of maturity, and duration of debt; indexing more debt to prices, and reducing indexation to policy interest rates, or the exchange rate; issuing fixed-coupon instruments; and, making judicious use of alternative financial instruments, in addition to coordinating monetary policy, and public debt management, so that reserve requirements may be lowered, leading to more efficient cash markets.